A Safe and Simple Method for Minimally Invasive Harvesting of the Partial-Thickness Quadriceps Tendon-Bone Autograft - Daisuke Kubota, M.D.; Hiroteru Hayashi, M.D., Ph.D.; Eitaku Koh, M.D.; Tomohiro Kayama, M.D., Ph.D., M.B.B.S., B.Sc.; Toshiyuki Omori, M.D.; Teruyuki Miyasaka, M.D., Ph.D.; Taiki Neyatani, M.D.; Mitsuru Saito, M.D., Ph.D. (Arthroscopy Techniques)
Good long-term postoperative clinical results can be achieved after anterior cruciate ligament reconstruction using the quadriceps tendon (QT) as the graft. Anatomical rectangular tunnel anterior cruciate ligament (ACL) reconstruction is performed using a ribbon-shaped quadriceps tendon with bone (QTB) harvested in partial layers, considering that harvesting the transplanted tendon in all layers, including the joint capsule, may delay recovery from postoperative pain and muscle weakness. However, no consistent method for harvesting the QTB graft tendon has been established. Moreover, the harvested tendon lacks length and thickness, and there is a risk of patellar fracture. Here, we describe a relatively easy and safe technique for QTB harvesting that uses a special cutter capable of harvesting tendon components of a certain width, thickness, and length, and an instrument to remove a fixed amount of bone fragments using a cannulated drill.